Pelatihan Proses Pelaksanaan Perencanaan Pembelajaran Harian di PAUD Al-Amin - Sitorus, Ahmad Syukri; Nasution, Adelia Hanjani; Putri, Fadhillah Salsabila; Pohan, Isra’ Mianda; Rambe, Saimanur Putri; Br.Tarigan, Agitha Fitriana; Rahmawati, Lia; Regina, Syindi Alshifa; Safitri, Cindi Juliana (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This activity aims to describe the understanding of PAUD teachers on lesson planning and improve the pedagogic and professional competence of PAUD teachers. With this activity, teachers must realize that they can't just make a learning plans but must really understand what they have created. And with this training, teachers can increase their insight or ability in designing play activities in PAUD. The type of research used is qualitative research. This research conducted at Al-Amin PAUD, Telaga Tujuh Village, Labuhan Deli. The research design is phenomenology. The data sources in this study were informants consisting of the committee and Al-Amin PAUD teachers. The implementation of this activity is using the training method. And the data collection technique in this training is documentation. The research results show that in designing or making RPPH the teachers are quite enthusiastic and begin to understand the preparation of RPPH. By understanding the RPPH, the teachers can become more confident and inrease their teaching skills. And teachers must really understand how the design process and designing learning plans are made attractive according to the characteristics and development of early childhood.